Measuring pro-environmental behavioural determinants using closed-answer surveys - Hunter Doughty; Laura Thomas-Walters (Oryx)
Changing human behaviours is a key facet of addressing global environmental issues. There are many factors (i.e. determinants) that could influence whether an individual engages in pro-environmental behaviour, and understanding these determinants can improve efforts to protect and restore the natural environment. However, despite published criticism of poor survey design, there is little practical guidance on how to capture these determinants accurately in closed-answer surveys (those with predefined answer options). A recent literature review summarized behavioural determinants of pro-environmental behaviour. We build on this by providing practical insights into how 17 key pro-environmental behavioural determinants can be measured through closed-answer surveys. We reviewed 177 papers published during 2013–2023 that met the criteria for inclusion. These papers captured 624 measurements of the 17 determinants. We found seven types of question formats used, including scales (Likert scales, semantic scales and a pictorial scale), multiple-choice questions (where respondents could select either one or more answer options), binary questions and ranking questions. We then synthesized design considerations both specifically for each format and more broadly across surveys. These considerations included using validated measures, reducing cognitive burden and biases (e.g. social desirability bias, order effects, recall bias), selecting the question format (e.g. different formats of multiple-choice or binary questions) and using best practices for scale questions. The insights collected through this review provide practical advice for developing closed-answer surveys that robustly and usefully measure key determinants of pro-environmental behaviour.